(3YUQI GdefLhOs - (3Ydj Hf jhfS GdYGedj GdfHGWjs
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf GdMeO ddg GdPi MUd ai GdYbhd hLhH eYQaJg s
(3BNQgG (B:s
(3hdjS dYde Gfabhg ef hgPG BNQ eG CQOfG EjQGOg hefJgi eG bUOfG GQJjGOg MGeOjf Gddg Ydi CaVGdg heUdjf Ydi QShdg hGdCcGQe s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3eUOQ GbJfGA GdCUd (B:s
(3BjI Gddg GdMcje GdYGeI (B_ (3GdfLa (B(361) s
Keywords: (3GdJhMjO hGdedd hGdfMds